If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(1 + -6x) = 150 (1 * -6 + -6x * -6) = 150 (-6 + 36x) = 150 Solving -6 + 36x = 150 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 36x = 150 + 6 Combine like terms: -6 + 6 = 0 0 + 36x = 150 + 6 36x = 150 + 6 Combine like terms: 150 + 6 = 156 36x = 156 Divide each side by '36'. x = 4.333333333 Simplifying x = 4.333333333
| 3x+10+105=13x+15 | | 43.4= | | W(2w-2)=420 | | 7-4(3-6n)=-125 | | x+7-4=15 | | 0.25/7 | | 6x-6(4x+2)=24 | | (5+6x)-6x= | | 110d=100d+40 | | 4=96 | | X+(2x+1)+(3x+2)= | | 85=25-4x | | x+3x+2x^2=840 | | 8/x=-20 | | a-24=-15 | | (a+c-e)f=(b+1000-c-f)e | | 0.125=g-4.4 | | 2x-1/5=5x-1/4 | | 16-r^2=0 | | 3x-2=-2(x+11) | | 15-6m+6m= | | 54+55=x+74 | | 29x-15= | | 25x-2=23x+2 | | 36x+128= | | 7p^2+24p+16=0 | | Cos(65)=10/x | | 43x+135= | | 8+3(1x-1)= | | 4x^2-4x+4=14 | | -2+6+2x=28 | | 2u^2+u-10=0 |